Cryptosporidium galli and novel Cryptosporidium avian genotype VI in North American red-winged blackbirds (Agelaius phoeniceus) - Chelladurai, Jeba Jesudoss; Clark, Mark E; Kváč, Martin; Holubová, Nikola; Khan, Eakalak; Stenger, Brianna L S; Giddings, Catherine W; McEvoy, John (Parasitology research, 2016)
Proventriculus and intestinal samples from 70 North American red-winged blackbirds (Agelaius phoeniceus; order Passeriformes) were examined for the presence of Cryptosporidium by PCR amplification and sequence analysis of the 18S ribosomal RNA (18S rRNA), actin, and 70-kDa heat shock protein (HSP70) genes. Twelve birds (17.1 %) were positive for the Cryptosporidium 18S rRNA gene: six birds were positive at the proventriculus site only and six birds were positive at the proventriculus and intestinal sites. Sequence analysis of the 18S rRNA, actin and HSP70 genes showed the presence of the gastric species Cryptosporidium galli in a single proventriculus sample and a closely related genotype, which we have named Cryptosporidium avian genotype VI, in all other positive samples. These findings contribute to our understanding of Cryptosporidium diversification in passerines, the largest avian order.
Keywords: Cryptosporidiosis; Passeriformes; proteiny tepelného šoku HSP70; Bird Diseases; Proventriculus; Red-winged blackbird; kryptosporidióza; Cryptosporidium galli; Genotype; RNA ribozomální 18S; Avian genotype VI; Animals; HSP70 Heat-Shock Proteins; zvířata; polymerázová řetězová reakce; RNA, Ribosomal, 18S; Spojené státy americké; Intestine; Cryptosporidium; Polymerase Chain Reaction; nemoci ptáků; Passerines; genotyp; United States